Nature and Values in Research - Teti Nurhayati; Rina Setiana (al-Afkar, Journal For Islamic Studies, 2025)
This article provides a comprehensive introduction to research, focusing on the definition, objectives, and basic steps involved in the research process. Research is considered a systematic effort to answer questions and solve problems, and can be divided into various types, such as quantitative, qualitative, and mixed-method research. By providing a basic understanding of the research process, this article aims to help readers, especially students and novice researchers, understand and apply the principles of effective research. It explores the key characteristics that define quality scientific research. These characteristics include objectivity, systematicity, replicability, and accuracy. Through a literature review, this study found that objectivity is the foundation that allows research results to be widely accepted, while systematicity provides a clear structure to the process of data collection and analysis based on the literature review. These findings are expected to provide guidance for researchers and academics in conducting higher-quality research.